Risk management challenges in Malaysia’s landscape architecture project - S.Muthuveeran, Adam Aruldewan; Mohd Tahir, Osman; Ibrahim, Roziya; Mohd Noor, Mohd Zairul (e-International Publishing House, 2020)
This study aims to review current risk management challenges in Malaysia landscape architecture projects. This subject found to be lacking and yet essential to strategies for effective application. The data collection conducted through a semi-structured interview with twenty-four landscape architect professional based in the Klang Valley region. Then analysed using content and thematic analysis method. The research found that multiple challenges factor permits effective risk management application in the project. The study suggests for an extensive strategy to risk management application into the project to be formulated in enabling effective management of risk to improve project performances.